Bacteriophage therapy for multi-drug resistant Staphylococcus aureus infections within the airways - Iszatt, Joshua James (Curtin University, 2023)
This thesis supports the potential of phages in treating respiratory infections caused by Staphylococcus aureus bacteria, including MRSA. Phages Koomba kaat 1 and Biyabeda mokiny 1 demonstrated broad ranges of activity and remained stable when aerosolised. Genomic characterisation ensured contaminant free samples whilst in vitro and in vivo models validated their safety. Collectively, this study provided crucial preclinical insight, supporting their use for clinical trials to treat S. aureus respiratory infections.